A parallel decoding algorithm for LZ2 data compression - De Agostino, Sergio (Parallel computing, 1995)
The LZ2 compression method is hardly parallelizable since it is known to be P-complete. In spite of such negative result, we show in this paper that the decoding process can be parallelized efficiently on an EREW PRAM model of computation with O(n/log(n)) processors and O(log2n) time, where n is the length of the output string.